2022
DOI: 10.1186/s13578-021-00741-y
|View full text |Cite
|
Sign up to set email alerts
|

Y chromosome is moving out of sex determination shadow

Abstract: Although sex hormones play a key role in sex differences in susceptibility, severity, outcomes, and response to therapy of different diseases, sex chromosomes are also increasingly recognized as an important factor. Studies demonstrated that the Y chromosome is not a ‘genetic wasteland’ and can be a useful genetic marker for interpreting various male-specific physiological and pathophysiological characteristics. Y chromosome harbors male‑specific genes, which either solely or in cooperation with their X-counte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 171 publications
(216 reference statements)
0
5
0
Order By: Relevance
“…Sex dimorphism is an unavoidable feature in a plethora of diseases including HCC, and it can dictate susceptibility, severity, outcomes, and response to therapy. Data mining and case studies of HCC specimens have identified several Y-linked proto-oncogenes 41 and possible epigenetic modifications such as histone methylation 42 to discern sex differences. Sex-biased molecular signatures in HCC have focused on sex hormones, ie, androgen and estrogen.…”
Section: Discussionmentioning
confidence: 99%
“…Sex dimorphism is an unavoidable feature in a plethora of diseases including HCC, and it can dictate susceptibility, severity, outcomes, and response to therapy. Data mining and case studies of HCC specimens have identified several Y-linked proto-oncogenes 41 and possible epigenetic modifications such as histone methylation 42 to discern sex differences. Sex-biased molecular signatures in HCC have focused on sex hormones, ie, androgen and estrogen.…”
Section: Discussionmentioning
confidence: 99%
“…[ 21 ]One notable advantage of CSY stems from the Y-chromosome's classification as “the genetic wasteland” [ 44 ],referring to the perception that the Y-chromosome contains fewer genes compared to other chromosomes and is therefore less biologically significant [ 44 ]. Yet, recent research has shown that the Y-chromosome could still play a role in certain biological processes and disease susceptibility, albeit to a lesser extent than other chromosomes [ 45 ]. The concept of the Y-chromosome as a "genetic wasteland" may still hold true in terms of overall gene content, but specific genes could still have important effects on health and disease.…”
Section: Discussionmentioning
confidence: 99%
“…LOY is one of the most well-characterized mCA because it is large (~ 60 Mb) and relatively easy to detect in peripheral blood. For many years, LOY was thought to be part of normal male aging, but recent studies have shown that the Y chromosome plays a role beyond male development [ 46 ]. These functions may partially explain sex differences in disease and cancer predisposition [ 47 ].…”
Section: Discussionmentioning
confidence: 99%